PENGARUH PMA, PMDN DAN PAD TERHADAP ANGGARAN BELANJA DI PROVINSI KEPULAUAN BANGKA BELITUNG TAHUN 2002-2017 - Adita Oktaria Pane; Mohammad Faisal Abdullah; Arfida Boedirachminarni (Program Studi Ekonomi Pembangunan, 2020)
Investments in an area can improve existing economies, both foreign investment and domestic capital investment. With the increasing economy there will increase revenue in an area anyway, so that with increasing income in an area can affect the budget. In addition, it can be seen from the level of investment in an area. The purpose of this research is to know the development of investment in Bangka Belitung Islands Province and how to influence the budget in Bangka Belitung Islands Province. Data used in the form of secondary data can be downloaded through the official website of BPS and DPMPTSP (Investment office and integrated one Door service) with a period of 16 years using multiple linear regression analysis techniques with Using Test T, Test f and coefficient of determination. The results gained that foreign investment was not significant and negatively affected the budget, domestic capital investment was not significant but positively influential towards the budget and significant local revenue Positive impact on the budget.